Novelties in secretory structures and anatomy of Rhynchosia(Fabaceae) - VARGAS,WANDERLEIA DE (2015)
A comparative anatomical study was carried out on the secretory structures of leaflets from taxa belonging to the genus Rhynchosia - taxa difficult to delimit because of uncertain interspecific relations - in order to evaluate the potential diagnostic value of these anatomical traits for taxonomic assignment. A further objective was to establish consensual denomination for these secretory structures. The new anatomical features found in these taxa were sufficiently consistent to separate the species evaluated. The presence and localization of glandular-punctate structures bulbous-based trichomes, the number of layers in the palisade parenchyma and the arrangement of vascular units distinguish the taxa investigated and these characteristics can be extended to other species of Papilionoideae. The trichomes analyzed were described and classified into five types. Depicted in diagrams, photomicrographs, and by scanning electron microscopy, and listed for the first time at the genus and species levels. The information obtained served to effectively distinguish the taxa investigated among species of Papilonoideae.